Securitization and house price growth - Genevieve Nelson (Danmarks Nationalbank, 2021)
From 2000-2006 U.S. house prices and mortgage credit grew while the relative cost of mortgage credit fell - particularly for privately securitized mortgages - suggesting a credit supply expansion. This paper explores two (credit supply) shocks: an increased inow of global savings into the United States, and innovations in the securitization of mortgage credit. I model the interaction of financially constrained commercial banks and mortgage securitizers, generating a novel balance sheet effect: changes in the distribution ofaggregate mortgage credit quantity are linked to changes in mortgage spreads. Only innovation in securitization (direct relaxation of the securitizers' financial constraint) matches mortgage market dynamics.
Keywords: G21; G23; E21; E44; 330; Housing Finance; Financial Sector; USA